Answer:
Option (C)
Explanation:
Given expression is 4(x + x + 7) - 2x + 8 - 4
When x = 1,
Value of the expression will be,
= 4(1 + 1 + 7) - 2(1) + 8 - 4
= 4(9) - 2 + 8 - 4
= 36 - 2 + 8 - 4
= 38
For x = 2,
= 4(2 + 2 + 7) -2(2) + 8 - 4
= 44 - 4 + 8 - 4
= 44
Now we will check the same for the given options.
Option (A). For x = 1,
6x + 11 = 6(1) + 11
= 17
For x = 2,
6x + 11 = 6(2) + 11
= 23
Option (B). For x = 1,
3(x + 7) = 3(1 + 7)
= 24
For x = 2,
3(x + 7) = 2(2 + 7)
= 18
Option (C), x = 1
2(3x + 16) = 2[3(1) + 16]
= 38
For x = 2,
2(3x + 16) = 2[3(2) + 16]
= 44
Option (D), For x = 1,
= 19
For x = 2,
2(3x + 16) = 2[3(2) + 16]
= 44
Since value of the expression for x = 1 and 2 matches with the value in option (C)
Therefore, Option (C) will be the answer.